KOMUNIKASI DAKWAH: Interaksi Dan Integrasi Media Sosial - Suharto, Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Communication  media  is a  media  that  has  mastered  the global world. Various forms of media designed to facilitate communication including social media such as twitter, facebook, mailing lists and  other. In the context of da'wah communication, social media is very possible for the use of propaganda.  Interact through social media to do da'wah or sosialization Islamic teachings and  even  the  integration of social media in communication becomes very important mission for the ease of public access to information about Islam, to  motivate people to  learn more in-depth and form image of Islam or to counter-information the insult and understimate Islam.